2012
DOI: 10.1021/la300696z
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Substrate-Supported Membranes from Mixtures of Long- and Short-Chain Phospholipids

Abstract: We studied the formation of substrate-supported planar phospholipid bilayers (SPBs) on glass and silica from mixtures of long- and short-chain phospholipids to assess the effects of detergent additives on SPB formation. 1,2-Hexyanoyl-sn-glycero-3-phosphocholine (DHPC-C6) and 1,2-heptanoyl-sn-glycero-3-phosphocholine (DHPC-C7) were chosen as short-chain phospholipids. 1-Palmitoyl-2-oleol-sn-glycero-3-phosphocholine (POPC) was used as a model long-chain phospholipid. Kinetic studies by quartz crystal microbalanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 38 publications
0
39
0
Order By: Relevance
“…In Fig. 4A 30 in their studies of POPC/DHPC bicelles coating glass surfaces also suggested that DHPC was absent from the deposited bilayer.…”
Section: Electrospray Ionization Mass Spectrometry (Esi-ms)mentioning
confidence: 82%
See 1 more Smart Citation
“…In Fig. 4A 30 in their studies of POPC/DHPC bicelles coating glass surfaces also suggested that DHPC was absent from the deposited bilayer.…”
Section: Electrospray Ionization Mass Spectrometry (Esi-ms)mentioning
confidence: 82%
“…[28][29][30] Bicelles, or bilayered micelles, are biomimetic model membranes consisting of mixtures of long-chain and short-chain amphiphiles. The long-chain amphiphiles assemble into a planar lipid bilayer stabilized at its edges by the short-chain amphiphiles.…”
mentioning
confidence: 99%
“…Photopolymerizations of (meth)acryl and dienoyl bearing zwitterions must be subsumed under photo-initiated radical polymerization. Yet, the topochemical polymerization of conjugated diynes ("diacetylenes") producing strongly colored polymers is unique (Scheme 9), and has been continuously used for stabilizing lipid model membranes [30][31][32][359][360][361][362][363][364][365][366][367][368][369]. Scheme 9.…”
Section: Synthesis By Chain Growth Polymerizationsmentioning
confidence: 99%
“…Partial disruption of liposomes with detergent has also been successfully used to facilitate vesicle rupture. Detergents have been used previously to assist vesicle fusion to solid [21] or polymer surfaces [22] .…”
Section: Additional Informationmentioning
confidence: 99%